Manejo de la escoba de bruja (Moniliophthora Perniciosa) en el Cultivo de Cacao CCN-51 (Theobroma cacao L.) en la Hacienda” San José zona de Babahoyo - Espinoza Rodríguez, Dennis Ariel (2019)
The cultivation of cocoa is a tropical plant that is grown for its almond-shaped seeds, which are used to make chocolate, also called cocoa tree or cocoa tree. The investigations during the twenty years, between 1895-1913, the country remained the first cocoa exporter to provide 15-25% of the international demand. The information obtained generates the importance of collecting information based on the management of witch broom disease in the Cocoa crop, which aims to find solutions and provide necessary information that demonstrates the benefit of controlling the disease in the cocoa crop. Preventive control is essential to avoid the presence of disease. This research work was carried out in the San José farm, located on the Chilintomo road, province of Los Ríos. In the San José farm, the disease known as the Witch's Broom was identified, which is a fungus that affects the entire cocoa plantation, normally the witch's broom is visible because it has the shape of a broom originating from a deformation of the growth points of the plant and if there is no good cultural control in the plantation, the ears would be affected. In order to detect the presence of this disease, the cocoa producer of the San José farm conducts sampling, with the purpose of detecting the degree of affectation in the cocoa plantation. The parameters that determine the employees of the San José farm are the formation of witch brooms in the plant, deformation in the fruits, and the correct cultural control that is being applied in the plantation in the case of phytosanitary pruning. During the monitoring of the Hacienda San José, cocoa plants that were affected by pernicious Moniliophthora were visualized, generating deformations at the growth points. Therefore it is necessary to perform monitoring and evaluation during their cycles. Using different types of plant protection and maintenance pruning, in turn, apply fungicides to prevent diseases